Peran Filsafat Hukum dalam Pembangunan Hukum Indonesia - Supriadin, Bambang (Equality : Jurnal Hukum dan Keadilan, 2026)
This paper discusses the nature of legal philosophy and its strategic role in legal development in Indonesia. Legal philosophy, as a branch of philosophy, aims to understand and critically examine the concept of law in depth, as well as to seek the foundations of justice, legal certainty, and the utility of law. In the Indonesian context, legal philosophy is essential for shaping a legal system that aligns with societal values, meets community needs, and guarantees human rights. By examining various schools of legal philosophy, this paper demonstrates that sound lawmaking must be based on philosophical reflection. This approach not only provides a normative direction for legislative development but also strengthens institutional structures and the value orientation of law in society. Therefore, legal philosophy serves as an essential foundation for creating a just, rational, and contextual legal system withim Indonesia’s national legal framework.